2022
DOI: 10.1177/08902070211044552
|View full text |Cite
|
Sign up to set email alerts
|

The Extended Social Relations Model: Understanding Dissimilation and Dissensus in the Judgment of Others

Abstract: The Social Relations Model (SRM), which has been an important tool for personality researchers, presumes the variabilities in the SRM components, perceiver, target, and relationship effects, are consistent across perceivers and targets. We introduce the extended SRM (eSRM) to examine individual differences in the variances of each component of the SRM. We explore the tendency for perceivers to see targets in different ways, Dissimilation, and the tendency for targets to be viewed in different ways, Dissensus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…In the classic SRM, this possibility is not given because the model assumes homoscedasticity of residuals. However, a recent extension to the SRM proposed by Kenny et al, (in press) relaxes this assumption, thus enabling an examination of perceiver differences in dissimilation (how variable they see other people) and target differences in dissensus (how variable they are seen by other people). Applying these concepts to PD research may uncover additional instances of how interpersonal dysregulation manifests interpersonally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the classic SRM, this possibility is not given because the model assumes homoscedasticity of residuals. However, a recent extension to the SRM proposed by Kenny et al, (in press) relaxes this assumption, thus enabling an examination of perceiver differences in dissimilation (how variable they see other people) and target differences in dissensus (how variable they are seen by other people). Applying these concepts to PD research may uncover additional instances of how interpersonal dysregulation manifests interpersonally.…”
Section: Discussionmentioning
confidence: 99%
“…This type of design is technically not a round-robin (because professionals would not be asked to rate one another) but a block design, thus requiring slightly different statistical treatment (cf. Kenny et al, 2006). Nevertheless, patients' own reports on their experience would not only be complemented by several others' reports of the patients' experiences but also by the patients' perceptions of multiple others and by the reports of multiple others on their own experiences with these patients.…”
Section: Practical Considerationsmentioning
confidence: 99%
“…Perceivers generally reach some level of consensus about what Mia is like, especially if they have access to similar cues about her and share similar meaning systems about those cues. Nonetheless, it has been shown that consensus is higher for some targets than for others (Kenny, 2004; Kenny et al, 2023). Perceivers might agree more about Mia’s personality than about Mark’s personality.…”
Section: Does the Good Metaperceiver Exist?mentioning
confidence: 99%
“…
Objective. People differ in how positively they tend to see others' traits, but people might also differ in how strongly they apply their perceptual styles (Kenny et al, 2023). In two studies (Ns = 355, 303), the current research explores individual differences in how variable people's first impressions are across targets (i.e., within-person variability), how and why these differences emerge, and who varies more in their judgments of others.
…”
mentioning
confidence: 99%
“…For example, if Pam perceives Tim positively on some trait, part of her perception can be attributed to her general tendency to see people in positive ways on that trait. These tendencies, called perceiver effects, essentially describe individual differences in people's average impressions of other people (Kenny, 2019), but perceivers might also differ in how much their impressions vary across targets (Kenny et al, 2023). Take the example of Pam and Polly who both see others in more positive ways on average than most people do on the trait intelligence.…”
mentioning
confidence: 99%